Law and development in East and Southeast Asia - Antons, Christoph (RoutledgeCurzon--IIAS Asian studies series., 2003)
An examination of prospects for commercial law reform in Asia, considering Japan and Singapore as role models for Asian developmentalism, and development related business laws in China, Korea, Indonesia, Malaysia, Vietnam and the Philippines.